Terrorism and trade - Volker Nitsch; Dieter Schumacher (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
This paper examines the effect of terrorism and warfare on international trade. We investigate bilateral trade flows between more than 200 countries over the period from 1960 to 1993. Applying an augmented gravity model that includes several measures of terrorism and largescale violence, we find compelling evidence that terrorist actions reduce the volume of trade; a doubling in the number of terrorist incidents is associated with a decrease in bilateral trade by about 4 percent.
Keywords: F19; F15; 330; Terrorism; Conflict; Warfare; Trade; Politische Gewalt; Aussenwirtschaft; Internationale Wirtschaftsbeziehungen; Schätzung; Welt